Окремі аспекти організації та діяльності Міжвідомчої комісії з міжнародної торгівлі у контексті проведення антидемпінгових, антисубсидиційних та спеціальних розслідувань - Ковальчук, Н.М. (Часопис Київського університету права, 2009)
В статье проведено теоретическое исследование и предложено пути решения отдельных аспектов деятельности Межведомственной комиссии по международной торговле. Проанализированы роль и место Межведомственной комиссии по международной торговле в числе других органов проведения антидемпинговых, антисубсидиционных и специальных расследований. Дано определение этой институции, исследована процедура ее организации и разработаны предложения относительно усовершенствования отечественного законодательства. Ключевые слова: Межведомственная комиссия, антидемпинговое расследование, антисубсидиционное расследование, специальное расследование. The present article provides theoretical research and presents ways of solving of some aspects of activity of Interdepartmental commission of international trade. It determines role and place of this institution among other bodies which conduct anti-dumping, anti-subsidizing and safeguard investigations. The definition of Interdepartmental commission of international trade is created. Author research the procedure of organization of this body and propose the recommendations for the improvement of proper legislation. Key words: Interdepartmental international trade commission, аnti-dumping investigation, аnti-subsidizing investigation, special investigation.